Overexpression of a WRKY Transcription Factor TaWRKY2 Enhances Drought Stress Tolerance in Transgenic Wheat - Gao, Huiming; Wang, Yafei; Xu, Ping; Zhang, Zhengbin (Frontiers in Plant Science, 2018)
Drought is a major environmental stress that severely restricts plant growth and crop productivity. A previous study showed that TaWRKY2 from wheat (Triticum aestivum) plays an important role in drought stress tolerance. In the present study, we isolated the promoter of TaWRKY2 and identified multiple regulatory cis-elements in the promoter region. The activity of the TaWRKY2 promoter was induced by drought, salt, heat and ABA. We also generated TaWRKY2-overexpressing transgenic wheat,and found that the transgenic seedlings exhibited significantly enhanced tolerance to drought stress, as evidenced by a higher survival rate and lower water loss rate of detached leaves compared to wild-type(WT) plants. In addition, the transgenic lines had higher contents of free proline, soluble sugar and chlorophyll.During a prolonged period of drought stress before the heading stage, the growth of WT plants was inhibited, whereas the TaWRKY2-overexpressing lines progressed to the heading stage. The increased grain yield of the transgenic wheat lines reflected the cumulative effects of longer panicle length, more kernels per spike, and greater aboveground biomass. Our findings show that TaWRKY2 can enhance drought tolerance and increase grain yield in wheat, thus providing a promising candidate target for improving the drought tolerance of wheat cultivars through genetic engineering.